Motivation for tourism entrepreneurship: overview based on bibliometric analysis of empirical research (2023)
Although motivation is key to tourism entrepreneurship, there are no current studies that describe this field of research. The objective of this bibliometric analysis was to evaluate the performance of empirical research on the motivation of tourism entrepreneurship (MET), and to identify its evolution, structure of intellectual influences and areas of study, based on different metric techniques and scientific mapping. It was carried out based on 38 articles published between 1989 and 2022 in journals indexed to Scopus, using statistical methods, the VOSviewer software and the Tree of Science tool. The findings reveal reduced global coverage of research. There are seven research streams that give structure to the empirical research of the MET, where lifestyle has been a transversal theme and the motivation for sustainable tourism entrepreneurship emerges. The results suggest strengthening this area and providing support for future research.